Real Real-time Aspect on the Application Implementation of Chronic Disease Management Program Patients in supporting Clinical Documentation Improvement (CDI) - Rinda nurul karimah; Sustin Farlinda; Lailatu Taufiqoh; Izatul Milla (Jurnal Teknologi Informasi dan Terapan, 2019)
Chronic Disease Management Program (PROLANIS) is one of programs conducted by Indonesian Healthcare Social Insurance Organization. Prolanis program’s target is making chronic disease patient achieve the optimal quality of life through the effective and efficient health service costs and prevent any disease complications [3]. Prolanis activities consist of medical or educational consultation, reminder, club activities and health-status monitoring which is done periodically. Clinical Documentation Improvement (CDI) is a program facilitating the realization of patients’ accurate clinical-status. Prolanis application was made to monitor the health status patients periodically. An evaluation must be done especially on real-time aspect to make prolanis application perfect. This research was descriptive and quantitative analytic research with cross sectional approach by using scoring method. The research results revealed that the value of information quality on real-time aspect regarding the implementation of prolanis application on overall score interpretation was in good category (79,3%%). The highest real-time aspect was found in the patients’ identity items written on BPJS cards and the health chart was 83,3%, while the lowest item of personnel data and DM report was 73,3%. These analysis results can be used to make prolanis application more perfect so that it will fulfill the needs of CDI.